Mongolia : Strategies for Enforcing Wildlife Trade Regulations in Ulaanbaatar - World Bank (Washington, DC, 2017)
This report reviews and recommends strategies to regulate the trade of wildlife through Ulaanbaatar, Mongolia. Ulaanbaatar is an ideal site to launch an effort to support improved enforcement of wildlife trade regulations. The city is the seat of Mongolia's government, media markets, and civil society, as well as the center of the wildlife trade. Some of the country's largest raw materials markets are located to the east and west of the city. Ulaanbaatar's many road inspection points, its train station, and its airport are all strategic sites for enforcing trade regulation. Responsibility for enforcement of wildlife trade regulations is distributed among half a dozen different agencies. This report focuses specifically on Mongolia's existing legal framework for controlling the wildlife trade, and on strategies for improving enforcement, particularly in Ulaanbaatar. Before turning to those subjects, the next section provides a brief overview of the Mongolian wildlife trade.